Role of WD40 repeat proteins in the regulation of the Snf1 kinase complex during energy stress - (:unkn) unknown (My University, 2024)
The ability to respond to energy stress is critical to maintain energy homeostasis (balance) in living organisms. Protein kinases of the AMP-activated protein kinase (AMPK) family serve as master regulators of energy homeostasis in eukaryotes. Because of their importance, these kinases are conserved in organisms as diverse as yeast and humans.The general outline of AMPK function is very intuitive. When energy levels become low, AMPK becomes activated and aims to balance the energy “budget”. To this end, AMPK takes measures to cut energy spending and increase energy income. Specifically, AMPK inhibits ATP-consuming anabolic processes and stimulates ATP-producing catabolic mechanisms. The importance of AMPK is hard to overestimate. Defects in AMPK signaling in humans can lead to diseases ranging from metabolic syndrome to obesity to type 2 diabetes to cancer. Therefore, it is not surprising that the AMPK signaling pathway is an attractive drug target. For example, metformin – a drug used to treat type 2 diabetes – works by stimulating AMPK signaling. Despite such importance, not all aspects of mammalian AMPK signaling are fully understood. In part, this is due to the complexity of the system. Therefore, additional knowledge can be gained from studying AMPK in model organisms. Historically, a lot of knowledge regarding AMPK function has come from studies with budding yeast, Saccharomyces cerevisiae. The S. cerevisiae ortholog of mammalian AMPK is known as Snf1 (sucrose non-fermenting 1) protein kinase. It is equivalent to mammalian AMPK both functionally and structurally. Glucose is the most preferred carbon/energy source for yeast cells. When yeast cells experience energy stress, the Snf1 kinase becomes activated and stimulates the utilization of alternative carbon/energy sources that are less preferred than glucose; the kinase will also slow down cell proliferation. Like mammalian AMPK, the yeast Snf1 protein kinase is a heterotrimeric αβγ complex consisting of a catalytic α subunit (Snf1), one of three alternative scaffolding/targeting β subunits (Sip1, Sip2, or Gal83), and a stimulatory γ subunit (Snf4). The three alternative β subunits define three related but distinct Snf1 kinase complexes called Snf1-Sip1, Snf1-Sip2, and Snf1-Gal83. The Gal83 subunit is the most abundant of the three β subunits. Moreover, Gal83 targets Snf1 to the nucleus to regulate transcription. The present work focuses primarily on Snf1-Gal83. Until now, Snf1/AMPK kinase complexes have been assumed to assemble “by themselves”. In this work, we present evidence that two WD40 repeat proteins interact with Snf1 and Gal83 and function in a chaperone-like manner to promote the integrity of the Snf1-Gal83 complex. Our findings also raise the possibility that these WD40 repeat proteins could similarly stimulate the Snf1-Sip2 and Snf1-Sip1 complexes. Thus, we have uncovered an entirely new level of eukaryotic Snf1/AMPK regulation. Our findings may have implications for AMPK regulation in other eukaryotes and inform research in human metabolic disease, fungal pathogenesis, and yeast biotechnology.
Keywords: AMP-activated protein kinase; Energy stress; Gal83; Saccharomyces cerevisiae; Snf1 protein kinase; Stress-response